BEAUTY OF COLORS IN PAINTING: चित्रकला मे रंगों का सौन्दर्य - Rajalakshmi (International Journal of Research -GRANTHAALAYAH, 2014)
Blue sky, greenery, colorful flowers and beautiful animals and birds spread all around. Amazing work of God and beautiful color combination. It seems as if God as a painter has made a beautiful depiction on the canvas of this world through its colors and lines. If colors are not included in the illustration, then will this world still look so beautiful? maybe no. Everything that a human sees through his eyes is comprised of colors, so it would not be wrong to say that colors are of paramount importance in life and this color gives us to the top of taste or pleasure through its beauty and charm. Take away, because joy is the essence of the whole creation and also the ultimate culmination of heartfelt feelings. नीला आकाश, चारों तरफ फैली हरियाली रंग-बिरंगे फूल एवं सुंदर-सुंदर पशु-पक्षी। ईश्वर की अद्भुत कृति एवं सुंदर रंग संयोजन। ऐसा प्रतीत होता है कि मानो भगवान चित्रकार के रूप में इस संसार रूपी कैनवास पर अपने रंगों एवं रेखाओं के माध्यम से एक सुंदर चित्रण कर दिया हैं। अगर चित्रण में यदि रंगों का समावेश न हो तो क्या तब भी तब भी यह संसार इतना ही सुंदर दिखेगा? संभवतः नहीं। मनुष्य अपने नेत्रों के माध्यम से जो कुछ भी देखता उनमें रंगों का समावेश होता ही है, अतः यह कहना सर्वथा गलत नहीं होगा कि जीवन में रंगों का स्थान सर्वोपरि है और यही रंग हमें अपने सौन्दर्य व आकर्षण के माध्यम से रसास्वादन या आनंदानुभूति के शीर्ष तक ले जाते हैं, क्योंकि आनन्द भाव सम्पूर्ण सृष्टि का सार है और हृदयगत् भावनाओं की अन्तिम परिणति भी।